UNIVERSAL ARC FURNACES AND MIXERS OF DIRECT CURRENT OF NEW GENERATION FOR ORGANIZATION OF HIGH-EFFICIENT FOUNDRY AND METALLURGICAL PRODUCTIONS - V. S. Malinovskij; V. D. Malinovskij; I. V. Vlasova (Литьë и металлургия, 2009)
Universal arc furnaces and mixers of constant current of new generation for organization of high-efficient foundry and metallurgical productions, developed by ООО «NTF «Ekta» are presented.